Acromegaly With an Ectopic Clival Pituitary Adenoma: Case Report and Review of Literature. Issue 1 (February 2015) - Wan, Yingfeng; Xie, Dajiang; Yang, Shuxu; Wang, Kun; Xue, Zhaoliang; Guo, Songxue; Wang, Yirong
Abstract : Ectopic pituitary adenomas usually occur within the sphenoid sinus or nasopharynx and seldom within the clivus. In this report, we describe the fourth case of ectopic growth hormone (GH)-secreting adenoma in the clivus. A 49-year-old female patient was admitted with acromegaly and blurred vision. Biochemical evaluation revealed a notable elevation in the GH level at >40 ng/mL (normal range, 0.0 to 5.0 ng/mL). A magnetic resonance imaging scan of the pituitary showed a mass below the sellar turcica. The patient underwent an endoscopic transnasal transsphenoidal approach to the sella, and the tumor in the clivus was completely removed. The tumor was separated from the intrasellar contents by intact bone of the sella. Histologic examinations of the resected tumor showed a chromophobe pituitary adenoma, and immunocytochemistry was positive for GH adenoma. Including our case, only 16 reported ectopic adenomas have occurred in the clivus. Relevant literature is briefly reviewed.